News site blocks (Egypt) - Voidly (Voidly Global Censorship Index, 2017)
CRITICAL severity censorship detected in Egypt. Data sourced from OONI.
Censorship Incident ID: EG-2017-0001. Severity: critical. Confidence: 90%